Acquired IFNγ resistance impairs anti-tumor immunity and gives rise to T-cell-resistant melanoma lesions - Antje Sucker (Nature Portfolio, 2017)
IFNγ secretion by CD8+T cells is critical for immunotherapy efficacy. In this study, the authors show that melanoma patients can become resistant to immunotherapy by acquiring chromosomal alterations and subsequent inactivating mutations in genes of the IFNγ signalling cascade, most often JAK1 or JAK2.